2006
DOI: 10.1186/1471-2334-6-83
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureusprevalence: Current susceptibility patterns in Trinidad

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) has become one of the most widespread causes of nosocomial infections worldwide. Recently, reports have emerged that S. aureus strains recovered from community-acquired infections are also methicillin-resistant. This study was undertaken to analyze the prevalence of methicillin resistance among isolates at a regional hospital in Trinidad, and document the current resistance profile of MRSA and methicillinsensitive Staphylococcus aureus (MSSA) to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 28 publications
6
46
2
Order By: Relevance
“…Thus, risk of infection is high in individuals occupationally exposed to wounds or wound dressing or doctor's mobile phones indicating a need to screen individuals in hospitals for risk exposures and infections, to avoid outbreak and cross infections (Panlilio et al, 1992). In present study MRSA isolation rate was high, 77% (27/35), in HA sources (wound/pus and doctor's mobile phone) but Rajaduraipandi et al, (2006), Orrett and Land (2006), Perwaiz et al, (2007) reported it 31, 60 and 32% MRSA in their studies respectively and in CA sources it was 50% MRSA which is similar with findings of Orrett and Land (2006).…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, risk of infection is high in individuals occupationally exposed to wounds or wound dressing or doctor's mobile phones indicating a need to screen individuals in hospitals for risk exposures and infections, to avoid outbreak and cross infections (Panlilio et al, 1992). In present study MRSA isolation rate was high, 77% (27/35), in HA sources (wound/pus and doctor's mobile phone) but Rajaduraipandi et al, (2006), Orrett and Land (2006), Perwaiz et al, (2007) reported it 31, 60 and 32% MRSA in their studies respectively and in CA sources it was 50% MRSA which is similar with findings of Orrett and Land (2006).…”
Section: Resultsmentioning
confidence: 49%
“…In India, MRSA is more in hospital population (patient and staff) as carrier than in the community (Vidhani et.al. 2001) and one of the common causes of hospital-acquired wound infections either after accidental injury or surgery and these strains generally show multiple drug resistance, which limits treatment possibilities (Anupurba et al, 2003, Nadig et al, 2006, Orrett and Land, 2006. Now days, medical professionals extensively use mobile phones which may get contaminated through the hands or when used carelessly in ICU or surgical wards which may act as a source of MRSA to patients and may also pose a danger in spread of infection in the community (Khivsara et al, 2006, Deccan Herald, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…These different rates among MRSA from different countries may be attributed to variations in patient populations, the biological characteristics of the S. aureus strains, and/or infection control practices (Orrett & Land, 2006) In this study, the frequency of MRSA carriage varied between different departments. The prevalence was highest in MICU and it was followed by SICU, which was close to the results that were obtained by Altınbas et al (2013).…”
Section: Discussionmentioning
confidence: 88%
“…Amikacin was found to be able to exert an antibacterial effect on all the bacterial strains under study. Aminoglycosides (Amikacin, Gentamycin, (2006) and Orrett & Land (2006). While, Bhat et al (1990) found that the variation in the antibiotic sensitivity pattern of the isolated organisms, may be related to several factors including differences in pH value, condition and time of incubation, composition and nature of the culture media, size of inoculum, source of isolated organism and perhaps differences in strain activity.…”
Section: Resultsmentioning
confidence: 99%